Droughts, Dry Spells and Low Water Levels in Late Medieval Hungary (and Slavonia) III: Potential Dry Spells and the Drought of (1516-)1517 - Kiss, Andrea (Journal of Environmental Geography, 2019)
As a continuation of the series about droughts in late medieval Hungary, we present, analyse and compare further cases, based on contemporary direct and indirect documentary source evidence. The data, concerning (potential) low water-level conditions in 1375, 1378, 1393-1394 and 1517, and the economic problems (and solutions) probably related to multiannual dry (spring, summer?) conditions, recorded in the 1410s and 1420s, are further compared to the recent tree-ring based hydroclimate reconstruction of the OWDA (Old World Drought Atlas). Whereas the cases in 1371, 1375, 1378, (1414-)1417 and 1427-1428 (and before) reflect on local-regional problems and also show some conflicts between documentary and tree-ring based reconstructions, in 1393 the local data and the potential Danube low water-level evidence mainly reflects on lower precipitation sums in Western Hungary and the Upper-Danube catchment. The 1517 case, however, presumably refers to large-scale drought problems in the Carpathian Basin and beyond. Beyond the case studies on individual years or multiannual periods, indirect indicators of drought and dry spells are discussed and main groups of most frequent (potential) indicators defined. Preceded by a hard winter, the year of Reformation stands out both in documentary and tree-ring evidence as an outstanding drought year, and has particular importance in the paper.